1999
DOI: 10.1161/01.res.85.9.787
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the Zinc Finger Transcription Factor BTEB2 Gene by Egr-1 Through Mitogen-Activated Protein Kinase Pathways in Vascular Smooth Muscle Cells

Abstract: Abstract-We have recently demonstrated that a developmentally regulated zinc finger protein, basic transcription regulatory element binding protein 2 (BTEB2), is induced in neointimal smooth muscle in response to vascular injury. In this study, we investigated the molecular mechanisms regulating BTEB2 expression in vascular smooth muscle cells (SMCs) in vitro. BTEB2 mRNA expression is rapidly and persistently induced in SMCs by phorbol 12-myristate 13-acetate (PMA) and basic fibroblast growth factor. We have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
81
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 46 publications
15
81
0
Order By: Relevance
“…It has also been reported that AT2R inhibits the activity of ERK. Several observations indicate that the ERK pathway activates the BTeB2 promoter (29). The present study found that the inhibition of ERK1/2 is linked to the downregulation of BTEB2.…”
Section: Discussionsupporting
confidence: 70%
“…It has also been reported that AT2R inhibits the activity of ERK. Several observations indicate that the ERK pathway activates the BTeB2 promoter (29). The present study found that the inhibition of ERK1/2 is linked to the downregulation of BTEB2.…”
Section: Discussionsupporting
confidence: 70%
“…survivin) [74] or proproliferative pathways (e.g. mitogen-activated protein kinases) [75] that are activated following vessel injury can, in turn, augment KLF5 expression. These key observations suggest that KLF5 may be an important regulator of the SMCs response to vascular injury.…”
Section: Klf5mentioning
confidence: 99%
“…For example, vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) were shown to be potent activators of KLF5 in vitro (Kawai-Kowase et al, 1999;Hoshino et al, 2000;Ogata et al, 2000). Activation of KLF5 expression has also been linked to the Wnt/Wg signaling pathway.…”
Section: Introductionmentioning
confidence: 99%